2001
DOI: 10.1034/j.1600-0404.2001.103002082.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits in young patients with Parkinson's disease

Abstract: The higher rate of depression explains our finding of more "harm avoidance" among young PD patients. According to a literature review the choice and performance of controls is crucial whether personality traits in PD patients may be assessed as abnormal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 28 publications
0
32
1
Order By: Relevance
“…Our findings are consistent with studies that did not show an overall association between PD and personality traits related to introversion and extroversion preceding the onset of motor symptoms. 11,12 However, our findings are in contrast with some case-control studies that showed an association. 2,5,6 These case-control studies may be limited because of a possible cause-effect inversion, whereby the personality traits observed may have been consequences (or early manifestations) of PD rather than risk factors.…”
Section: Resultscontrasting
confidence: 56%
“…Our findings are consistent with studies that did not show an overall association between PD and personality traits related to introversion and extroversion preceding the onset of motor symptoms. 11,12 However, our findings are in contrast with some case-control studies that showed an association. 2,5,6 These case-control studies may be limited because of a possible cause-effect inversion, whereby the personality traits observed may have been consequences (or early manifestations) of PD rather than risk factors.…”
Section: Resultscontrasting
confidence: 56%
“…Of these studies, seven reported significantly lower NS in PD patients compared to HC [13,[31][32][33][34][35][36]. One study did not report any difference for NS between PD patients and HC [37].…”
Section: The Psychobiological Model Of Cloninger and Parkinson's Diseasementioning
confidence: 95%
“…Finally, age as a significant covariate of personality style is relevant since behavioural and associated acquired personality changes may in part be age-related. It has been hypothesized that any personality changes associated with PD are more pronounced in older rather than younger people with PD, likely due to more extensive dopaminergic, noradrenergic and serotonergic pathway changes in older individuals [49].…”
Section: Discussionmentioning
confidence: 99%